(3GdeYJHQ aj GdMceIs - (3gHI Gddg Hf Ydj Hf edcG GdHdOj, CHh GdHQcGJ,J (B560 (3g` s ((3eMeO Hf CHj GdahGQS Hf CHj SYO s)
(3ChdgG (B:s
(3Ghd GdehLhO efg GdebGdI GdKGdKI ai Yde GdbjGS GdaUd GdChd ai JCdja GdbVGjG HYVgG Ydi HYV Ydi UhQI jSJaGO HYdegG GdMGUd s
(3BNQgG (B:s
(3aeG dGaUd HGdSeGY hGdfXQ hGdNHQ Hd HeTGgOg GdGQhGM hSeGY fWbgG hQDjI GLSGOgG GdQhMjI hEdi gPG jfJgi HfG GdfXQgG gfG s
(3HgG GKGQ JeRbs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B74s
Keywords: (3GdadSaI hGdefWbs